The Relationship Between Sports Hall Management Quality and Community Sports Participation - Rahman, Muhamad Fathur; Setya Rahayu (Al-Qalam Institue, 2025)
This study aims to examine the relationship between the management quality of the Sports Hall (GOR) and the level of community participation in sports. A mixed-methods approach was employed with an explanatory sequential design. Quantitative data were collected through questionnaires, while qualitative data were gathered through semi-structured interviews. The findings revealed that the management quality was generally good, particularly in administrative and public service aspects. However, shortcomings were noted in facility maintenance and the disposal of unfit equipment. Community participation was relatively low, with a participation index of 0.47 for GOR-based activities and 0.60 for outdoor sports. The Spearman correlation test indicated a positive and significant relationship between management quality and sports participation (r = 0.295; p = 0.003). These results suggest that enhancing GOR management quality could foster greater community engagement in physical activity. The implications for education are significant, as improved sports facility management can contribute to creating more inclusive and accessible environments for students, promoting physical education and active lifestyles.